Learning Transformation in the Digital Era: The Role of Technology in Improving the Quality of Education Digital Transformation - Halim Dwi Putra; Renta Maranata Sirait; Linda Sari; Lukman Affandi; Adela Anita (Postgraduate, University of Mataram, 2026)
Digital transformation has brought significant changes to various sectors of life, including education. The development of information and communication technology has driven a paradigm shift in learning from conventional models to digital-based learning that is more flexible, interactive, and student-centered. This article aims to analyze the role of technology in improving the quality of education through learning innovation, accessibility, and the effectiveness of the teaching and learning process. The method used is a literature study with a descriptive-analytical approach through a literature review of various academic journals and books. The results of the study indicate that the use of digital technologies such as Learning Management Systems (LMS), online learning, artificial intelligence, and interactive multimedia contributes to increasing student engagement, equalizing access to education, and strengthening 21st-century competencies. However, this transformation also faces challenges such as the digital divide, human resource readiness, and ethical aspects of technology use. Therefore, integrated policies and implementation strategies are needed to ensure that technology truly improves the quality of education.